THE EFFECTS OF AN INDIVIDUALIZED, SELF-PACED SCIENCE PROGRAM ON SELECTED TEACHER, CLASSROOM, AND STUDENT VARIABLES—ISCS LEVEL ONE. - Lashier Jr., W. S.; Nieft, J. W. (Journal of Research in Science Teaching, 1975)
The article presents a study on the use of the Intermediate Science Curriculum Study (ISCS) Level One program concerning its effectiveness upon the teacher, student, and classroom. It was concluded that ISCS Level One is designed to allow the student to do many experiments as an aid in arriving at meaningful concepts. When a comparison of the perceptions of classroom activity was made between high and low ISCS achievers, a significant difference was obtained for the classroom variables of student participation in the classroom, and laboratory activities.